Therapeutic Application of Mesenchymal Stem Cells Derived Extracellular Vesicles for Immunomodulation - Gomzikova, Marina O.; James, Victoria; Rizvanov, Albert A. (Frontiers in Immunology, 2019)
Immunosuppressive potential of mesenchymal stem cells has been extensively investigated in many studies in vivo and in vitro. In recent years, a variety preclinical and clinical studies have demonstrated that mesenchymal stem cells ameliorate immune-mediated disorders, including autoimmune diseases. However to date mesenchymal stem cells have not become a widely used therapeutic agent due to safety challenges, high cost and difficulties providing long term of production. A key mechanism underpinning the immunomodulatory effect of MSCs is the production of paracrine factors including growth factors, cytokines, chemokines and extracellular vesicles (EVs). MSCs derived EVs have become an attractive therapeutic agent for immunomodulation and treatment of immune-mediated disorders. In addition to many preclinical studies of MSCs derived EVs, their beneficial effects have been observed in patients with both acute graft-versus-host disease and chronic kidney disease. In this review, we discuss the current findings in the field of MSCs derived EVs-based therapies in immune-mediated disorders and approaches to scale EV production for clinical use.